Efficient removal of emerging contaminant sulfamethoxazole in water by ozone coupled with calcium peroxide: Mechanism and toxicity assessment. (November 2021) - Xiang, Liangrui; Xie, Zhehao; Guo, He; Song, Jiaxi; Li, Dongsheng; Wang, Yawen; Pan, Shijia; Lin, Siying; Li, Zhen; Han, Jiangang; Qiao, Weichuan
Abstract: Sulfamethoxazole (SMX) is a widely distributed emerging contaminant, which will bring serious harm to ecology and human health. Herein, evaluation of ozone (O3 ) coupled with calcium peroxide (CaO2 ) for SMX elimination was carried out. The results showed that CaO2 could promote SMX elimination in O3 system. The removal efficiency was improved from 65.6% to 73.9% when the CaO2 dosage was 0.06 g L −1 . O3 dosage of 0.55 g h −1 was beneficial to SMX degradation. With decrease of initial SMX concentration, the removal of SMX firstly enhanced and then declined. Compared with alkaline, acidic and neutral conditions were favorable for SMX degradation. ROS including ·OH, ·O2 − and 1 O2 play critical role for SMX degradation. Synergetic effect could be established between O3 and CaO2, which encouraged formation of ·OH and accelerated SXM decomposition. The total organic carbon (TOC) and chemical oxygen demand (COD) were all declined after O3 /CaO2 treatment. According to results of liquid chromatography-mass spectrometry (LC-MS) and references, four major pathways were proposed. The O3 /CaO2 technology was also suitable for practical wastewater treatment. QSAR calculation and seed germination experiment showed that toxicity of the treatment solution was alleviated after O3 /CaO2 treatment. Graphical abstract: Image 1 Highlights: O3 was coupled with CaO2 for synergetic removal of SMX in water. Performance of SMX elimination under various parameters was investigated. The synergetic effect was explored by the formation of H2 O2, O3 and ·OH. The degradation process was inspected by UV–Vis, 3DEEMF spectra and LC-MS. O3 /CaO2 technology for practical wastewater treatment was explored.